2011
DOI: 10.1007/bf03253160
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Bacillus amyloliquefaciens BY01 with High Productivity of Menaquinone for Cheonggukjang Production

Abstract: To develop a cheonggukjang with high content of menaquinone (MK), bacterial strains were isolated from good quality cheonggukjang, and MK productivities of isolated strains were determined by high-performance liquid chromatography. After sensory evaluation and MK determination, a potential probiotics, BY01, with acceptable sensory quality and high productivity of MK was isolated. Fermentation under aerobic condition produced more MK than that obtained under anaerobic condition, and the synthesized MK mainly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…This result was in contrast with the previous reports that the majority of MK-7 production was during the logarithmic growth phase of B. subtilis natto (Berenjian et al, 2011). Wu and Ahn (2011) have reported that the amount of the intracellular MK-7 is larger than that of extracellular MK-7. However, the intracellular MK-7 can be released into the extracellular fraction by forming an intracellular complex with protein during the culture process (Armougom et al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
“…This result was in contrast with the previous reports that the majority of MK-7 production was during the logarithmic growth phase of B. subtilis natto (Berenjian et al, 2011). Wu and Ahn (2011) have reported that the amount of the intracellular MK-7 is larger than that of extracellular MK-7. However, the intracellular MK-7 can be released into the extracellular fraction by forming an intracellular complex with protein during the culture process (Armougom et al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
“…3). Two strains with a sequence identity of greater than 99 % should be classified as the same species according to Wu and Ahn (2011). It is difficult for B. pumilus and B. mojavensis, having a B. subtilis-like phenotype, to be distinguished from B. subtilis.…”
Section: Molecular Biological Identifications Based On 16s Rrna Gene mentioning
confidence: 99%
“…Many microorganisms can be used to biosynthesize MK-7, such as Escherichia coli, 7 Sphingobacterium multivorum, 8 Bacillus amyloliquefaciens 9,10 and Bacillus subtilis. [11][12][13] However, commercial production of MK-7 is mainly done through extraction from natto, a type of food, rather than via microbial fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…14 This is because the fermentative production of MK-7 is too low. 9,[11][12][13] Fortunately, the biosynthetic pathway of MK-7 has been claried at present (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%